2022
DOI: 10.1161/circoutcomes.122.008942
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Preexisting Cardiovascular Disease and Death and Cardiovascular Outcomes in Critically Ill Patients With COVID-19

Abstract: Background: Preexisting cardiovascular disease (CVD) is perceived as a risk factor for poor outcomes in patients with COVID-19. We sought to determine whether CVD is associated with in-hospital death and cardiovascular events in critically ill patients with COVID-19. Methods: This study used data from a multicenter cohort of adults with laboratory-confirmed COVID-19 admitted to intensive care units at 68 centers across the United States from March 1 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 50 publications
4
19
0
Order By: Relevance
“…Nevertheless, complete case analysis gives unbiased results when the chance of being a complete case is independent of outcome after taking covariates into account, even when data are missing not at random. 26 Our findings extend those from previous smaller studies of individual cardiovascular risk factors and COVID-19 outcomes, 27,28 supporting a strong association between raised cardiovascular risk profile and severe COVID-19 outcomes. While a previous Mendelian randomisation study, which by design avoids reverse causation and most confounding, failed to show an association between some genetically-predicted cardiovascular risk factors (blood pressure, BMI, type 2 diabetes and coronary artery disease) and COVID-19 hospitalisation, 29 estimates had wide confidence intervals and did not capture full profiles of either cardiovascular risk or severe COVID-19 outcomes.…”
Section: Additional Analysessupporting
confidence: 86%
“…Nevertheless, complete case analysis gives unbiased results when the chance of being a complete case is independent of outcome after taking covariates into account, even when data are missing not at random. 26 Our findings extend those from previous smaller studies of individual cardiovascular risk factors and COVID-19 outcomes, 27,28 supporting a strong association between raised cardiovascular risk profile and severe COVID-19 outcomes. While a previous Mendelian randomisation study, which by design avoids reverse causation and most confounding, failed to show an association between some genetically-predicted cardiovascular risk factors (blood pressure, BMI, type 2 diabetes and coronary artery disease) and COVID-19 hospitalisation, 29 estimates had wide confidence intervals and did not capture full profiles of either cardiovascular risk or severe COVID-19 outcomes.…”
Section: Additional Analysessupporting
confidence: 86%
“…Our studies further identified a dose-response relationship between increased cardiovascular risk factors and the risk of COVID-19. This dose-response effect may represent a cumulative effect of multiple risk factors on the occurrence and severity of COVID-19 [27] . Further prospective cohort studies are needed to determine potential causal associations.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms by which pre-existing CVD disorders impact the risk of COVID-19 are not fully understood. Inflammation, multiorgan dysfunction, vascular injury, and metabolic and endothelial disarray may play a role in the risk of COVID-19 [3] , [27] . For example, studies have shown that excess adiposity and cardiometabolic disorders may increase the risk of COVID-19 and the severity of the disease outcomes by increased risks of inflammation, immune dysfunction, hypercoagulation, and mechanical obstruction [3] , [4] , [28] , [29] , [30] .…”
Section: Discussionmentioning
confidence: 99%
“…Third, pre-existing CVD is strongly associated with a poor outcome of COVID-19 infection, and the mortality of the COVID-19 positive patients with underling CVD comorbidities is substantially high. [37][38][39][40] Therefore, it is possible that the increase in patients with CVD who died from COVID-19 in 2020 (and who were not considered as dying of CVD) could partly explain the decrease of CVD in-hospital deaths in 2020. Finally, a direct effect of COVID-19 infection on CVD cannot be discarded, as it was estimated that a 10% COVID-19 prevalence could lead to up to 62 410 excess deaths in England.…”
Section: Cardiac Risk Factors and Preventionmentioning
confidence: 99%